2020
DOI: 10.1007/s00259-020-05084-3
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis changes in COVID-19 survivors with persistent symptoms: an [18F]FDG-PET/CT study

Abstract: Purpose Several patients experience unexplained persistent symptoms after SARS-CoV-2 recovering. We aimed at evaluating if 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) was able to demonstrate a persistent inflammatory process. Methods Recovered adult COVID-19 patients, who complained unexplained persisting symptoms for more than 30 days during the follow-up visits, were invited to participate in the study. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
121
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 10 publications
(9 reference statements)
4
121
0
4
Order By: Relevance
“…The relationship between COVID-19 severity and increased odds of persistent symptoms may be explained by the immune response to the SARS-CoV-2 virus which stimulates the production of cytokines and other inflammatory mediators, with higher concentrations found in those with a more severe clinical form [3,[26][27][28]. The multi-systemic inflammatory response to the virus may also be responsible for persistent COVID-19 symptoms in survivors [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between COVID-19 severity and increased odds of persistent symptoms may be explained by the immune response to the SARS-CoV-2 virus which stimulates the production of cytokines and other inflammatory mediators, with higher concentrations found in those with a more severe clinical form [3,[26][27][28]. The multi-systemic inflammatory response to the virus may also be responsible for persistent COVID-19 symptoms in survivors [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an astounding 78% of study subjects had abnormal cardiac MRI findings (41). Sollini and colleagues used positron emission tomography/computed tomography (PET/CT) to demonstrate that SARS-COV-2 infection could also induce vasculitis, which again was correlated with patients' prolonged symptoms (71). In a study of 538 COVID-19 survivors (median age of 52.0 years (IQR 41.0-62.0), 54.5% female) followed for median time of 97.0 (ranging from 95.0-102.0) days from discharge to first follow-up, Xiong et al found that 13% of patients complained of persistent cardiovascular symptoms (20).…”
Section: -C) Cardiovascularmentioning
confidence: 99%
“…Since patients with COVID-19 infection suffer from such vascular complications, it is likely that this imaging modality will be of great value in assessing cerebrovascular injuries. Also, it is possible that COVID-19-related vasculitis can be detected by FDG-PET imaging [29,30]. In a recent study, Sollini M et al evaluated scans of 10 Fig.…”
mentioning
confidence: 99%
“…From the left to the right are the FDG-PETs 41 days after the PECCT, 47 days before, and 9 days after the positive BLE Duplex, which demonstrate improvement from 47 days before with visualization of bilateral CF and PV only, and 13 days before and 94 days after the negative BLE Duplex for acute DVT, which demonstrate progression of visualization of bilateral CF, PV, left PT, and left peroneal. BLE, bilateral lower extremities; CF, common femoral; DVT, deep vein thrombosis; PE, pulmonary embolism; PECCT, chest computed tomography with PE protocol; PT, posterior tibial; PV, popliteal vein; UE, upper extremity (reproduced with permission from Zhu HJ et al) [23] patients who had recovered from COVID-19 and assessed evidence for systemic inflammation by FDG-PET/CT imaging [30]. These investigators compared the findings in patients with those of control subjects with cancer but with negative follow-up FDG-PET/CT scans.…”
mentioning
confidence: 99%
See 1 more Smart Citation